Análise energética de cerveja eleborada com mel - Brunelli, Luciana Trevisan [UNESP]; Venturini Filho, Waldemar Gastoni [UNESP] (EIA Energy in Agriculture, 2013)
The objective of this study was to characterize energetically beersmade withhoney. The tests of beer production weremade withninetreatments,threecombination of the originalextract concentrations (11, 13and 15 °Brix) and threepercentagesof honeyin the wort formulation(0, 20 and 40%).The experimentwas completely randomizedwith two replications, totaling eighteenplots.Themashingprocesswas performed byinfusion, with honey added in the boiling step. After clarified, the wort had its extract contents corrected with the addition of filtered water and was inoculated withlowfermentation yeast .The fermentation occurred at 10 ° C. The beer was manually bottled and stored in a freezer at 0 °C for 15 days, formaturation. The beers were chemically analyzed on proximate composition (moisture, protein, lipid, ash, and carbohydrate), alcohol content (% m / m) and then calculated the energy value. The results ofchemical analysis andenergetic valuesof the beerswere subjected to analysisof variance (F test) and the means werecompared byTukey testat 5% probability. The commonbeershad the lowestenergy value (31.05 to 31.95 kcal100g-1) in relation toextra(36.42 to 38.42 kcal100g-1) and strong(38.20 to 40.17 kcal100g-1) beers. Theincrease in the original extractin beerraises theircaloric values. The presenceof honeyin the formulationincreasedthe energetic valuesincommon andextrabeersand decreasedin strong.The levelsof alcohol andcarbohydratewere predominant in thebeer energetic values,beingpossible to observeadirect relation amongthese components ofbeer and theircaloric value.

O objetivo deste trabalho foi comparar os teores de nutrientes (carboidratos, proteínas e gorduras totais) e valores energéticos informados nos rótulos de bebidas não-alcoólicas comerciais de manga e de goiaba com os resultados encontrados em análises laboratoriais e padrões estabelecidos pela legislação brasileira. Dentre as bebidas de manga, foram analisadas quatro marcas de sucos tropicais não adoçados, três adoçados, seis néctares convencionais e três light. Dentre as de goiaba, quatro sucos tropicais não adoçados, três adoçados, cinco néctares convencionais e três light. Os teores de carboidratos, proteínas e gorduras totais foram obtidos através de análise química dessas bebidas, enquanto que os seus valores energéticos foram estimados através de cálculo centesimal, utilizando fatores de conversão para carboidratos (4kcal/g), proteínas (4kcal/g) e gorduras totais (9kcal/g). As bebidas cujos teores de nutrientes e valores energéticos obtidos em laboratório excederam o intervalo de tolerância de ± 20%, calculado a partir dos dados declarados em suas embalagens, foram consideradas fora dos padrões de qualidade. Das dezesseis bebidas comerciais de manga analisadas, metade declarou os teores de nutrientes e valores energéticos, em conjunto, de maneira correta em seus rótulos. Enquanto que, das quinze de goiaba, cinco puderam ser consideradas dentro dos padrões de qualidade.
Energy analysis ofbeerproducedwith honey
Keywords: Alcoholic beverage; Chemical composition; Calorificvalue and energy value; Bebida alcoólica; Composição centesimal; Valor calórico e valor energético